The great debates in entrepreneurship - Kuratko, Donald F.; Hoskinson, Sherry (Advances in the study of entrepreneurship, innovation, and economic growth ;, 2017)
This volume presents some of the most important 'debates' that exist in the field of Entrepreneurship today. It brings together leading scholars, deriving contributions from special sessions designed by the Global Consortium of EntrepreneurshipCenters (GCEC) to discuss both sides of these 'great debates'. Topics include: "Is the Business Plan Really Dead and Should It Be?", "Does the Lean Start up Deserve all the Hype?", "Entrepreneurial Ecosystem - Weak Metaphor orGenuine Concept?", "Teaching vs. Doing", "Is there a Role for Lecture and Content in Entrepreneurship Education?", "Should Centers Be Controlled Centrally?", and "Is a Bachelor's Degree in Entrepreneurship Worth It?"